Strategies to Interpret Javanese Cultural Terms Made by Tourist Guides at Kasunanan Palace of Surakarta - Purnomo, Budi (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2020)
This study attempts to investigate the strategies to interpret Javanese cultural terms used by tourist guides at Kasunanan Palace of Surakarta. The study is intended to be a descriptive and qualitative nature. The data were collected by joining ten guided group tours in Kasunanan Palace and recording the tourist guides’ interpretation of Javanese cultural terms to tourists. To know the types of interpretation strategies, the Javanese cultural terms and their English interpretation were analyzed by Newmark’s strategies for dealing with a cultural gap (1998a). The research findings show that the strategies used by the tourist guides to interpret Javanese cultural terms from the most to the least are: (1) descriptive and functional equivalent, (2) cultural equivalent, (3) naturalization, (4) neutralization and (5) compensation. The findings imply that the interpretation strategies used by the tourist guides are essential to obtain interpretation products that have equivalence to the Javanese cultural terms to be preserved in this millennial era.